Fake Product Identification in E-Commerce Platform using Blockchain Technology - G, Santhiya; G, Lokesh (Journal of ISMAC, 2024)
The proposed fake product identification system employs blockchain technology to address the escalating issues of counterfeit goods. Utilizing a decentralized ledger, each product is assigned a unique identifier recorded on the blockchain, which includes important manufacturing details and origin information. Smart contracts streamline the verification process by executing predefined rules to confirm product authenticity. Integration with supply chain systems ensures real-time tracking, enabling consumers to trace a product’s journey from production to sale. Utilizing QR codes consumers gain direct access to blockchain records, empowering them to make informed purchasing decisions. The system’s decentralized nature ensures information immutability, providing a tamper proof solution for product authentication. Collaboration among stakeholders within the blockchain network creates a united front against counterfeiters, fostering a shared responsibility for maintaining supply chain integrity. This globally accessibly solution transcends borders, enhancing international cooperation in combatting counterfeit products and preserving brand credibility.